Advanced glycation end products cause RAGE‐dependent annulus fibrosus collagen disruption and loss identified using in situ second harmonic generation imaging in mice intervertebral disk in vivo and in organ culture models. Issue 4 (21st September 2020) - Hoy, Robert C.; D'Erminio, Danielle N.; Krishnamoorthy, Divya; Natelson, Devorah M.; Laudier, Damien M.; Illien‐Jünger, Svenja; Iatridis, James C.
Abstract: Aging and diabetes are associated with increased low‐back pain and intervertebral disk (IVD) degeneration yet causal mechanisms remain uncertain. Advanced glycation end products (AGEs), which accumulate in IVDs from aging and are implicated in diabetes‐related disorders, alter collagen and induce proinflammatory conditions. A need exists for methods that assess IVD collagen quality and degradation in order to better characterize specific structural changes in IVDs due to AGE accumulation and to identify roles for the receptor for AGEs (RAGE). We used multiphoton microscopy with second harmonic generation (SHG), collagen‐hybridizing peptide (CHP), and image analysis methods to characterize effects of AGEs and RAGE on collagen quality and quantity in IVD annulus fibrosus (AF). First, we used SHG imaging on thin sections with an in vivo dietary mouse model and determined that high‐AGE (H‐AGE) diets increased AF fibril disruption and collagen degradation resulting in decreased total collagen content, suggesting an early degenerative cascade. Next, we used in situ SHG imaging with an ex vivo IVD organ culture model of AGE challenge on wild type and RAGE‐knockout (RAGE‐KO) mice and determined that early degenerative changes to collagen quality and degradation were RAGE dependent. We conclude that AGE accumulation leads to RAGE‐dependent collagen disruption in the AF and can initiate molecular and tissue level collagen disruption. Furthermore, SHG and CHP analyzes were sensitive to collagenous alterations at multiple hierarchical levels due to AGE and may be useful in identifying additional contributors to collagen damage in IVD degeneration processes. Abstract : Multiphoton microscopy with second harmonic generation (SHG), collagen‐hybridizing peptide (CHP), and image processing analyses were used to characterize effects of advanced glycation end products (AGEs) on collagen quality and quantity in intervertebral disc annulus fibrosus (AF). High‐AGE diets increased AF fibril disruption and collagen degradation resulting in collagen loss in an in vivo dietary mouse model. An ex vivo IVD organ culture model of AGE challenge on wild type and receptor for AGE‐knockout (RAGE‐KO) mice with novel in situ SHG imaging determined this collagen degradation was RAGE dependent.